THE IPICS «OLDEST ICE» CHALLENGE: A NEW TECHNOLOGY TO QUALIFY POTENTIAL SITES - J. Chappellaz; O. Alemany; D. Romanini; E. Kerstel (Лëд и снег, 2015)
Among the priorities of the International Partnerships in Ice Core Sciences (IPICS) core project of Past Global Changes (IGBP/PAGES), drilling ice as old as 1.5 million years is probably the most emblematic challenge. The search for a potential site in Antarcticahosting such old ice in good stratigraphic order is under way. Here we propose an innovative way to rapidly qualify potential sites. We plan to build a probe able to drill down to bedrock within one field season. The probe will embed a laser optical instrument measuring in real time key parameters such as the water isotopic composition of the ice and the concentration of one or more greenhouse gases.